(untitled) (REMUNOM, 2024)
This article seeks to analyze the possibility of including, as a defendant in labor execution, a company that belongs to the same economic group, even without participation in the knowledge phase. The study aims to analyze the concept of economic group, addressing aspects of its formation, the joint responsibility of the economic group in the execution phase, the changes after reform 13,467/2017 and the constitutionality and legality of this inclusion. One of the most conflicting points in this discussion is whether this inclusion would constitute a violation of the constitutional principles of broad defense and contradiction due to the fact of non-participation in the knowledge phase. With the suspension throughout the national territory of labor executions related to this topic, we will analyze the feasibility of redirecting the execution by examining the jurisprudence, principles and legal provisions.